Historical Importance of Notes Regarding Kizilbashes in the Tax Record Books Kept in the Early 16th Century - Erpolat, Mehmet Salih (Journal of Alevism-Bektashism Studies, 2020)
Since the beginning of the 20th century, the subject of Kizilbashes (Red-Heads) and Kizilbashism has taken its place among the subjects that attract the attention of the scientific world and are discussed. Studies on the subject are increasing day by day in terms of number, variety and quality. In some of these studies, it is seen that Ottoman archive documents were used meticulously as a source. Especially, the archive documents about the provisions and lodges in the Mühimme Books kept in the Divanıhümayun, which was the centre of the Ottoman administration, constituted the main source of many studies.Tax (tahrir) record books are one of primary source of reference for social, economic, financial, legal, demographic, military, toponymy, religious and Sufism issues regarding to the Ottoman Empire Period. Researchers have analysed almost all of these record books and many of these records have been the subject of master’s and doctoral dissertations. Some of them were published as books. The data from these records have clarified many issues regarding the Ottoman Period. However, despite the publication of so many books, theses, articles and papers, there are some issues that are overlooked and not paid attention to.This paper will clarify the nature of the notes from the record books kept at the beginning of the 16th century, in which are mentioned the terms “Kızılbaş”, “Kızılbaş fetreti”, “Kızılbaş kıranı”, “Kızılbaş zamanı”, “surh”, “surh-serân” and “mâl-ı Sürh-serân”. With these terms, it will be possible to explain the viewpoint of the Ottoman Empire towards the Kizilbash with official documents.The nature of the tax collected under the name “Sürh-seran” (Kizilbashes) and “... mâl-ı Sürh-seran” will be explained in details. The term “… mâl-ı Sürh-serân” reveals the existence of an enforcement which proves that the Kizilbash-Turkmens migrated from some of their settlements in Anatolia.It is possible to see some concrete examples of the effects of the Ottoman-Safavid struggle on Ottoman official documents. In addition, the paper will give an insight into the effects on population movements and their results, and their reflections to the present. Thus, it is important to share with the public the importance of information and notes from archive records in order to better understand some of today’s economic, cultural, social and religious issues.With the explanation of these terms, it will be possible to see the effects of the Ottoman-Safavid struggle in Anatolia on the Kizilbash-Turkmen community living in sanjaks, such as Amid, Mardin, Arapkir, Ergani, Çermik, Siverek, Kiğı, Çemişgezek, Harput, Teke, Çorum, Canik and Mosul, in the light of the documents.This paper will analyse 22 short and some one-sentence notes that we identified on the subject. By means to these notes, it will be possible to see the viewpoint and to understand some of the enforcements of the Ottoman State administration towards the Kizilbashes at the beginning of the 16th century.
Keywords: Kizilbash; Sürh-serân; tax record books; Diyarbekir Province; Kizilbash migration